Influência da temperatura de solubilização nas propriedades mecânicas do aço Maraging 300 - Lima Filho, Venceslau Xavier de (2018)
The understanding of the relationship between mechanical properties and microstructure of ultra high strength steels remains a key problem in metallurgy with important consequences for the industry, notably those of high performance such as nuclear, petrochemical and aerospace. Maraging steels are a class of ultra high strength steels of special importance due to their performance. In this work, the effects of the solution treatment temperature on the mechanical properties of the maraging 300 steels were evaluated, in order to maximize their toughness without considerable detriment of their mechanical strength. Five solution treatment temperatures were evaluated over a one hour treatment time. The characterization of the mechanical properties was done by tests of Rockwell C hardness, Charpy-V impact toughness, NTS impact sensitivity, tensile and fracture toughness in plane strain. The microstructural characterization was performed by optical microscopy to determine the prior austenite grain size and microstructure analysis, scanning electron microscopy for analysis of the microstructure and fracture surfaces, X-ray diffraction and backscattered electron diffraction. The results obtained demonstrated a Hall-Petch type relationship between the solution treatment temperature and the mechanical tensile strength. Conversely, an increase in fracture toughness was observed with increasing solution treatment temperature. In this way it was possible to find a heat treatment condition in which it was possible to raise about 20% of the toughness with a loss of only 6% in the tensile strength.